Studi Analek Konfusius Tentang Allah berdasarkan Konsep Wahyu Umum - Herman; Fredy Simanjuntak; Fransiskus Irwan Widjaja; Noh Ibrahim Boiliu (Institut Agama Kristen Negeri Kupang, 2021)
The wisdom of Confucius as a great teacher of the Chinese nation has proven his hard work in studying nature and ancient scriptures to find values ?? that is valuable for human life. Apart from the fall of man into sin that damaged not only the relationship between man and God, but also with nature. The purpose of this paper is to review the abilities and efforts of Confucius in knowing God through general revelation so that an awareness is obtained that these creatures have an influence on the environment, have needs, and are needed by the environment. The method used is descriptive research with a qualitative approach, namely by describing completely Confucius' understanding of God recorded in the Holy Word (Confucius' Analects). This study concludes that Confucius' understanding of God from God's attributes expressed in general revelation is a gap in the gospel mandate associated with cultural mandates. This connects the pre-sin human image that allows a balance of a relationship between awareness of God, neighbor, and nature.